COLLECTIVE LEARNING IN A LEARNING ORGANIZATION: GROWING TEAM LEARNING CULTURE TO SURVIVE AND DEVELOP - Adi Suryani (Jurnal Sosial Humaniora, 2025)
A learning organization has a deep culture of learning. It is constantly encourage its member to learn. This learning activity is not only for adapting to the rapid changing of its internal and external environment, but also for growing. The effort of a learning organization to create a conducive learning climate can be indicated by training its members. Working towards a learning organization has both its strengths and drawbacks. The strengths are it can improve the organization performance and organization survival. However, learning too rapid can lead to learning stress. Moreover it can lead to harsh internal competition.